Applying Gamification to the Library Orientation: A Study of Interactive User Experience and Engagement Preferences. - Nourse Reed, Karen; Miller, A. (Information Technology & Libraries, 2020)
By providing an overview of library services as well as the building layout, the library orientation can help newcomers make optimal use of the library. The benefits of this outreach can be curtailed, however, by the significant staffing required to offer in-person tours. One academic library overcame this issue by turning to user experience research and gamification to provide an individualized online library orientation for four specific user groups: undergraduate students, graduate students, faculty, and community members. The library surveyed 167 users to investigate preferences regarding orientation format, as well as likelihood of future library use as a result of the gamified orientation format. Results demonstrated a preference for the gamified experience among undergraduate students as compared to other surveyed groups.